C-X-C Motif Chemokine 13 (CXCL13) Is a Prognostic Biomarker of Idiopathic Pulmonary Fibrosis - Vuga, Louis J. (American Thoracic Society, 2014)
Rationale: C-X-C motif chemokine 13 (CXCL13) mediates B-cell trafficking and is increased, proportionately to disease activity, in many antibody-mediated syndromes. Dysregulated B cells have recently been implicated in idiopathic pulmonary fibrosis (IPF) pathogenesis. Objectives: To determine if CXCL13 is associated with IPF progression. Methods: CXCL13 was measured in lungs by DNA microarray and immunohistochemistry, and in plasma by ELISA. Measurements and Main Results: CXCL13 mRNA was threefold and eightfold greater in IPF lungs (n = 92) compared with chronic obstructive pulmonary disease (COPD) (n = 191) and normal (n = 108) specimens, respectively (P < 0.0001). IPF lungs also showed increased CXCL13 staining. Plasma CXCL13 concentrations (pg/ml) were greater in 95 patients with IPF (94 ± 8) than in 128 subjects with COPD (53 ± 9) and 57 normal subjects (35 ± 3) (P < 0.0001). Circulating CXCL13 levels were highest in patients with IPF with pulmonary artery hypertension (P = 0.01) or acute exacerbations (P = 0.002). Six-month survival of patients with IPF in the highest quartile of plasma CXCL13 was 65 ± 10% versus 93 ± 10% in the others (hazard ratio, 5.5; 95% confidence interval, 1.8–16.9; P = 0.0008). CXCL13 increases by more than 50% in IPF serial assays, irrespective of initial values, also presaged respiratory failure (hazard ratio, 7.2; 95% confidence interval, 1.3–40.0; P = 0.008). In contrast, CXCL13 clinical associations in subjects with COPD were limited to modest correlations with FEV(1) (P = 0.05) and progression of radiographic emphysema (P = 0.05). Conclusions: CXCL13 is increased and is a prognostic biomarker in patients with IPF, and more so than in patients with COPD. This contrast indicates CXCL13 overexpressions are intrinsic to IPF, rather than an epiphenomenon of lung injury. The present data implicate CXCL13 and B cells in IPF pathogenesis, and support considerations for trials of specific B-cell–targeted therapies in patients with this intractable disease.